Bioorganometallic chemistry—from teaching paradigms to medicinal applications - Hartinger, Christian G.; Dyson, Paul J. (Chemical Society reviews, 2009)
In undergraduate level organometallic chemistry courses students are usually taught that organometallic compounds are toxic and unstable in air and water. While this is true of many complexes, some are also non-toxic and stable in air and water. Indeed, bioorganometallic chemistry, the study of biomolecules or biologically active molecules that contain at least one carbon directly bound to a metal, is a thriving subject, and air and water stability is a general pre-requisite. This interdisciplinary field is located at the borderline between chemistry, biochemistry, biology and medicine. In this tutorial review, various aspects of bioorganometallic chemistry are introduced, with the main emphasis on medicinal organometallic compounds. Organometallic therapeutics for cancer, HIV and malaria and other medicinal applications are described. It is also shown how rational ligand design has led to new improved therapies much in the same way that an organometallic chemist working in catalysis will design new ligands for improved activities.